2018
DOI: 10.1096/fj.201701449r
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 attenuates allogeneic graft rejection by suppressing miR‐21 biogenesis in macrophages and promoting M2 polarization

Abstract: ADAR1 (adenosine deaminase acting on double-stranded RNA 1) is an RNA-editing enzyme that mediates adenosine-to-inosine RNA editing events, an important post-transcriptional modification mechanism that can alter the coding properties of mRNA or regulate microRNA biogenesis. ADAR1 also regulates the innate immune response. Here, we have demonstrated that ADAR1 expression increased in LPS-stimulated macrophages. Silencing ADAR1 by using small interfering RNA in macrophages resulted in the pronounced polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…LPS was used to stimulate RAW 264.7 macrophages. The expression of ADAR1 was first increased and then decreased after day 2; this agrees with our previous observation that ADAR1 was increased within 24 h after LPS activation [10]. SOCS3 is a key molecule involved in the negative regulation of cytokines that signal through the JAK/STAT3 pathway.…”
Section: Adar1 Regulates Expression Of Il-6 In Macrophages Via Socs3supporting
confidence: 91%
See 2 more Smart Citations
“…LPS was used to stimulate RAW 264.7 macrophages. The expression of ADAR1 was first increased and then decreased after day 2; this agrees with our previous observation that ADAR1 was increased within 24 h after LPS activation [10]. SOCS3 is a key molecule involved in the negative regulation of cytokines that signal through the JAK/STAT3 pathway.…”
Section: Adar1 Regulates Expression Of Il-6 In Macrophages Via Socs3supporting
confidence: 91%
“…Our previous studies showed that overexpression of ADAR1 reduces the mortality of mice with infections [10]. We found that the levels of IL-6, TNF-α, IL-1β, and MCP-1 were significantly increased at 24 h after sepsis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This opposite observation may be caused by the immortalization and transformation of the cell line. miR-21 targets phosphatase and tensin homolog (PTEN), which inhibits the phosphoinositide 3-kinase (PI3K)/Akt pathway [37]. As one of the most extensively studied signaling pathways, the PI3K/Akt pathway is involved in almost every aspect of macrophage activation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…ADAR1 may regulate IFN pathway components by recoding editing [39][40][41]; in cancer models, site-specific RNA editing at some sites increased following stimulation with IFN [40]. The idea that ISG transcripts are particularly targeted by ADARs is notable in the context of the proposed central role of ADARs in meditating IFN response.…”
Section: Other Adar1 Effects On Innate Immunitymentioning
confidence: 99%